Effect of omega-3 fatty acid on contrast-induced nephropathy - Gunes Bolatli; Mahinur Ulusoy; Fatih Tas; Naci Omer Alayunt; Ismail Zarasiz (Український Журнал Нефрології та Діалізу, 2021)
Abstract. Renal failure that develops acutely after the use of iodinated contrast material is called "contrast-induced nephropathy". It is a complication with high morbidity and mortality risk. Current treatments are aimed at protecting kidney functions, new treatment methods are being researched. This study aims to demonstrate the therapeutic effects of omega-3 fatty acids on CIN, taking into account the possible clinical usage of iodinated contrast media and the benefits of omega-3 fatty acids.